2021
DOI: 10.1183/13993003.04548-2020
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infections in people with primary ciliary dyskinesia: neither frequent, nor particularly severe

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by SARS-CoV-2 has by March 2021 infected at least 115 million people worldwide and caused over 2.5 million deaths. People with pre-existing chronic health conditions are reportedly at high risk of catching the disease and of having a severe disease course [1–4]. Primary Ciliary Dyskinesia (PCD) is a multisystem, genetic disease which affects about 1 in 10 000 people and leads to chronic upper and lower airway disease, laterality defects, including congeni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 16 publications
0
23
1
Order By: Relevance
“…COVID-PCD is a participatory research project where people with PCD have an active role in all stages of research from the design of the study, its content, the piloting, and communication of results. Details about the study methods have been published [ 29 , 30 ]. In short, the COVID-PCD study includes persons of any age from anywhere in the world with a confirmed or suspected diagnosis of PCD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-PCD is a participatory research project where people with PCD have an active role in all stages of research from the design of the study, its content, the piloting, and communication of results. Details about the study methods have been published [ 29 , 30 ]. In short, the COVID-PCD study includes persons of any age from anywhere in the world with a confirmed or suspected diagnosis of PCD.…”
Section: Methodsmentioning
confidence: 99%
“…In May 2020, we set up an international participatory research study, COVID-PCD, to follow people with PCD during the COVID-19 pandemic [ 29 ]. By March 2021, 24 of 640 participants (3.8%) had reported a positive SARS-CoV-2 test but most reported mild or no symptoms [ 30 ]. However, they carefully shielded themselves by staying at home and avoiding public places.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used as a web-based questionnaire in the COVID-PCD study. [34,35] A potential bias for its use as a postal survey could be selection bias as patients more interested in research or with more severe symptoms might be more prone to participate. However, as the response rate was extremely high, the risk of this bias is low.…”
Section: Limitationsmentioning
confidence: 99%
“…COVID-PCD is a participatory research project where people with PCD play an active role at all stages of research, including study design and content, piloting, and communication of results. Details about study methods and initial results have been published previously [26,27]. In summary, COVID-PCD includes people of any age from any country with suspected or confirmed PCD.…”
Section: Study Design and Inclusion Criteriamentioning
confidence: 99%
“…To study the incidence and severity of COVID-19 in people with PCD, we set up a participatory study, the COVID-PCD, in collaboration with PCD support groups from all over the world [26]. First results from the study showed a low infection rate and mostly mild COVID-19 disease [27]. People with PCD were strongly recommended to get vaccinated against SARS-CoV-2; however, to date there is no information about vaccination willingness, vaccination uptake, and side effects among people with PCD.…”
Section: Introductionmentioning
confidence: 99%